ANALYSIS OF CUSTOMER SATISFACTION LAUNDRY BUSINESS IN SIAK SRI INDRAPURA - Ermansyah, Ermansyah; Ramadhani, Muthia (LPPM STMIK Dharmapala Riau, 2025)
This research is based on the laundry service business which is currently developing rapidly. Laundry businesses must have certain strategies to be able to provide progress to their business because there are many competitors in the laundry services sector. Therefore, service quality is very influential in attracting customer satisfaction. The very rapid development of the business world has had an impact on the progress of the Laundry business, because currently only Laundry has developed a delivery service compared to other laundries in Siak Regency . The purpose of this research is to determine the influence of customer experience, trust and service quality on customer satisfaction at Laundry in Siak Regency. In this research, the sample consisted of 96 respondents using purposive sampling techniques. The data analysis used in this research is quantitative using the multiple linear regression method. Based on the results of simultaneous tests, it can be seen that the influence variables Customer Experience, Trust, and Service Quality together influence customer satisfaction at Laundry in Siak Regency. Then, partially, from this test it can be seen that the influence variables of Customer Experience, Trust, and Service Quality have a significant effect on Customer Satisfaction. The R square value obtained was 0.660 or equal to 60.6%, while the remaining 39.4% was influenced by other variables not studied.